PRESTASI BELAJAR SISWA DITINJAU DARI DUKUNGAN SOSIAL ORANG TUA - Sri Anjariah (LPPM Universitas Proklamasi 45, 2006)
One hundred and thirty eight students grade eleventh participated on this research. It was expected that the students' academic performance was influenced by their parents* social supports Those supports consisted of providing relevant information, emotional encouragement, providing accurate evaluation, and providing learning facilities. It was found that die product moment correlation score was .290, p < .01. Indeed, this research has underlined the crucial parental influence on children's academic performance.